Anna Franchi: l'indocile scrittura Passione civile e critica d'arte - ZAGLI, ANDREA (Fonti storiche e letterarie - Edizioni cartacee e digitali, 2016)
Avanti il divorzio is undoubtedly a fundamental work for the history of women and civil rights. Anna Franchi is fighting, together with the socialists, both for freedom of choice and for the right to civil and political vote, which were denied to women. The texts also deal with the struggles for the right to work and for fair wages. Moreover, they present unpublished profiles of personalities who devoted their fight of little hope and much courage to the cause. Anna Franchi was also the first woman who believed in the movement of the Macchiaioli: she wrote the history of the artistic movement, got to know its interpreters and sought for them a market that recognised their value. The friendship with Giovanni Fattori and the correspondence with many painters are relevant: the letters reflect not only the artistic aesthetic of the Macchiaioli, but also their moods, relationships, travels, successes and many sad moments that were confided to Fattori's friend, Anna.